2014
DOI: 10.1111/den.12269
|View full text |Cite
|
Sign up to set email alerts
|

Modified bowel preparation regimen for use in second‐generation colon capsule endoscopy in patients with ulcerative colitis

Abstract: Using CCE-2, the modified bowel preparation regimen, with reduced volume has the potential to succeed in the evaluation of mucosal severity in UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…[111][112][113] In available CE systems, RAPID software (Given Imaging, Ltd) has been installed in the flexible spectral imaging color enhancement system, raising the possibility of improving the contrast of vascular and mucosal patterns. 113,114 Aihara et al 112 and we reported 111 enhanced visibility of prototype small-bowel CE equipped with whitelight light-emitting diodes selected specifically to increase Table 3 Modified bowel preparation for ulcerative colitis (reproduced from Usui et al 99 )…”
Section: Future Perspectivesmentioning
confidence: 88%
See 2 more Smart Citations
“…[111][112][113] In available CE systems, RAPID software (Given Imaging, Ltd) has been installed in the flexible spectral imaging color enhancement system, raising the possibility of improving the contrast of vascular and mucosal patterns. 113,114 Aihara et al 112 and we reported 111 enhanced visibility of prototype small-bowel CE equipped with whitelight light-emitting diodes selected specifically to increase Table 3 Modified bowel preparation for ulcerative colitis (reproduced from Usui et al 99 )…”
Section: Future Perspectivesmentioning
confidence: 88%
“…In patients without contraindications, sodium phosphate solution is recommended as a booster. In Japan, sodium phosphate solution is not available, and magnesium citrate is used instead . To improve patient acceptance, Hartmann et al .…”
Section: Colon Cementioning
confidence: 99%
See 1 more Smart Citation
“…Compared with NaP-based regimens, the completion rate is lower, yet the application of PEG as booster is still promising for its safety and further studies should be performed to evaluate how completion rate may be increased. Previously, magnesium citrate was applied as an emerging booster with completion rates of 55-85% (23,24). These fluctuating results emphasize the need for further research on magnesium citrate as a booster.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sodium phosphate solution can potentially cause aphthoid ulcers or active colitis that can mimic IBD. Hence, some studies used PEG‐only regimen, magnesium citrate as boost, or the use of ascorbic acid and Gastrografin. On the other hand, Hartmann et al .…”
Section: Bowel Preparation For Cce In Ibdmentioning
confidence: 99%